Teachers' attitude towards the use of ICT in the rural primary schools / Taka Poren - Poren, Taka (2009)
School teachers are regarded as important 'agent of change' in the present era of Information Revolution and Digitalization. However, it has always been perceived that the level of their attitudinal capabilities and mental readiness in terms of ICT Usages especially between teachers of urban and rural setting are presumed to be contrastively wide and distinctively disproportionate. Therefore, in view of such condition, a study is conducted to determine the distinctive divide that exists among such teachers, notably with specific reference to those who hailed from the rural primary school setting. The questionnaires were administered on 111 teachers from 12 primary schools of Bau district in Sarawak. Their proficiency level and attitudinal tendencies towards the use of ICT were measured by the use of Robertson (CAS) Scale which was adopted and adapted to fit into the Malaysian school setting. The analysis of the study has shown that the respondents were very competent in the use of the basic computer software such as Microsoft Word, Microsoft Powerpoint, Microsoft Excel, Explorer and Open Office. Besides that it was also found that the respondents generally exhibit positive attitudes towards the use of computers. On the other hand, the result also revealed a diminishing trend of anxieties among the respondents despite the fact that it had always been a prevalent issue of significant magnitude among teachers as shown in the past studies. The level of computer use among the respondents has also shown a remarkable improvement, especially for the purpose of preparing lesson plans, examination questions, analysis of examination results and the management of student's profile records.